Express Method of Field Measurements to Create a Three-Dimensional Model of an Ice Formations - Pisarev Sergey; Vergun A. P.; Berkut A. I.; Morozov F. P.; Morozov P. A.; Vorovsky P. (Russian Journal of Earth Sciences)
This article describes a new, efficient, and quick method for conducting field measurements to create a three-dimensional model of ice formations. The method involves the use of a total station geodetic instrument, a powerful LOZA georadar, and an unmanned aerial vehicle with a camera. The technique is especially useful for measuring unstable ice formations with horizontal dimensions ranging from 50 to 300 meters. Examples of applying this method during winter fieldwork on the Sakhalin Island's eastern shelf in 2019 are provided.